Corporate Environmental Responsibility and the Cost of Capital: International Evidence - El Ghoul, Sadok (Journal of business ethics, 2018)
We examine how corporate environmental responsibility (CER) affects the cost of equity capital for manufacturing firms in 30 countries. Using several approaches to estimate firms’ ex ante equity financing costs, we find in regressions that control for firm-level characteristics as well as industry, year, and country effects that the cost of equity capital is lower when firms have higher CER. This finding is robust to addressing endogeneity through instrumental variables, to using alternative specifications and proxies for the cost of equity capital, and to accounting for noise in analyst forecasts. We conclude that investment in CER reduces firms’ equity financing costs worldwide.